Prevalence and Factors Associated With Suicidal Ideation in Medical Students With Migraine - Luo, Jia-Ming; Liu, En-Zhuo; Yang, Hao-Di; Du, Cheng-Zhao; Xia, Li-Jie; Zhang, Zhi-Chao; Li, Tong; Ren, Jia-Jun; Tang, Jia-Qi; Tang, Pei-Qi; Tang, Yuan-Ru; Zhu, Shuang; et al. (Frontiers in Psychiatry, 2021)
【Abstract】：Background: The association between migraine and suicide ideation has been identified. However, the predictive factors of suicidal ideation are still controversial and whether migraine with aura can serve as an independent associated factor is uncertain. This manuscript studied the association between migraine with aura and suicidal ideation, and explored the predictive factors for suicidal ideation. Methods: We surveyed 9057 medical students and included 579 medical students with migraine into our study population. All students completed the General Situation Questionnaire, the Verified Headache Questionnaire, Hamilton Anxiety Scale (24 items), Hamilton Depression Scale (24 items), 36-item Health Survey Brief (SF-36), Headache Impact Text-6 (HIT-6), Test Anxiety Scale (TAS) and Pittsburgh Sleep Quality Index (PSQI). Suicidal ideation was measured by the Self-rating Idea of Suicide Scale (SIOSS). Results: Out of the 579 migraine medical college students, 562 (age 19.6±1.6; 448 women and 114 men) were included in the final study. The positive rate of suicidal ideation was 13.7%. Compared with students suffering from migraine without aura, those having migraine with aura had higher suicidal ideation (P＜0.015). After adjusting for demographic factors and headache characteristics, migraine with aura was found to be independently associated with suicidal ideation. Other independent associated factors include anxiety, depression, test anxiety, sleep, headache, and quality of life. Among these various factors, high quality of life was found to play a protective role against suicidal ideation. Conclusions: Migraine with aura is independently associated with suicidal ideation. Furthermore, anxiety, depression, text anxiety, poor sleep quality, and headache frequency are associated with suicidal ideation among medical college students with migraine.